Heavy Metal Concentration in Groundwater of Kirana Hill Region, Rabwah, District Chiniot, Pakistan - Iram, Shazia; Sultana, Rashida; Din, Maria Salah ud; Ahmad, Mirza Naseer; Shamrose, Zainab (International Journal of Economic and Environmental Geology, 2018)
The present study has been undertaken with an objective to evaluate the heavy metals concentration in groundwater of Rabwah town, Pakistan. The area is highly depending on groundwater sources for drinking purpose. Detailed analysis was carried out to understand the contamination level and distribution of heavy metals specifically lead, cadmium, zinc, nickel and transitional metal iron in drinking water during winter and summer. Twenty five surveyed private well sites located in Precambrian Kirana hills region were tested to map the groundwater quality and assess its suitability for drinking purpose. Detected amount of lead, cadmium and nickel were found higher than World Health Organization Standard maximum permissible limits, whereas the Ni levels were observed lower than the acceptable limit in some of the samples in summer. Generally, the mean metal concentration in sampled water sources have a descending order Ni>Pb>Cd>Zn>Cr in winter while Ni>Zn>Pb>Cr>Cd> Fe in summer. Water samples were highly enriched with Ni and Cr during summer and by Pb, Cd and Zn in winter. The quality of the drinking groundwater sources was observed unsafe for drinking; moreover, there is still need to take proactive measures to check the levels of heavy metals. The spatial analysis and distribution of groundwater quality in Rabwah town will make it easier for authorities and decision makers to determine the groundwater quality and recommend most suitable location for boring wells in future.